APPLICATION OF JIGSAW TYPE COOPERATIVE LEARNING MODEL IN IMPROVING STUDENTS' CRITICAL THINKING CAPABILITIES AND MASTERING THE CONCEPT OF AKIDAH AKHLAK IN MI PARANAKENG 2 - Nurlaila Nurlaila; Sulaiman Saat; Saprin Saprin (JICSA : Journal of Islamic Civilization in Southeast Asian, 2021)
This article discusses the application of the Jigsaw Cooperative Learning Model in Improving Students' Critical Thinking Skills and Mastery of Akhlak Concepts at Mi Paranakeng 2. This article uses a quantitative type of research, this study attempts to describe the current condition in a quantitative context. to determine the application of the independent variable, namely the Jigsaw recitation cooperative learning model on the dependent variable, namely the students' critical thinking ability and mastery of the concept of moral aqidah, and continued by calculating how much influence the independent variable had. In the learning process activities, the teacher or educator as the central figure of the teacher, and students as the subject of learning, are required to play a role in achieving educational goals in schools. At the same time, teachers and students are required in terms of knowledge, abilities, attitudes, so that the teaching and learning process can be carried out effectively and efficiently. The application of the jigsaw type of cooperative learning model at MI Paranakeng 2 was implemented properly and efficiently when researchers used it in teaching morals.